The effect of a combination of 40°c warm compress and handgrip exercise on spasm, pain, and anxiety in patients undergoing percutaneous coronary intervention - Mira Dwi Lantasary; Yenny Puspitasari; Agusta Dian Ellina (Politeknik Negeri Subang, 2026)
Background: Percutaneous Coronary Intervention (PCI) is an invasive procedure that often causes spasm, pain, and anxiety in patients, which can affect comfort and the smoothness of the procedure. Non-pharmacological interventions such as warm compresses and handgrip exercise have the potential to improve perfusion and reduce discomfort during the procedure. Purpose: To determine the effect of a combination of a 40°C warm compress and handgrip exercise on reducing spasm, pain, and anxiety, as well as improving perfusion index in patients undergoing Percutaneous Coronary Intervention (PCI). Methods: This study used a quasi-experimental design with a control group. A total of 30 respondents were divided into two groups: 15 in the intervention group and 15 in the control group. The intervention group received a combination of a 40°C warm compress and handgrip exercise, while the control group received standard care. Data were collected using spasm observation sheets, a perfusion index measurement tool, pain scales, and anxiety questionnaires. Data analysis was performed using the Wilcoxon and Mann–Whitney tests. Results: The findings showed that the combination of warm compress and handgrip exercise significantly reduced spasm, pain, and anxiety (p= 0.001< 0.05), and significantly increased the perfusion index (p= 0.000 < 0.05) compared to the control group. Patients in the intervention group demonstrated better physiological and psychological responses during the procedure Conclusion: The combination of a 40°C warm compress and handgrip exercise is an effective non-pharmacological intervention to reduce spasm, pain, and anxiety, while improving perfusion in patients undergoing PCI. This intervention can be recommended as a supportive nursing strategy to enhance patient comfort and procedural outcomes.